Shifting paradigm of urology residency after the COVID-19 pandemic in Indonesia - Kusuma, A.H. Wisda (Wolters Kluwer Medknow Publications, 2022)
Purpose: World Health Organization has declared coronavirus disease 2019 (COVID-19), a global pandemic in March 2020. Nations around the world enact prevention measures such as lockdowns, quarantines, massive testing, and tracing policies. Prevention measures against the pandemic may result in less opportunities for urology residents to learn. This study aims to investigate the difference in urology residency in Indonesia before and during the COVID-19 pandemic. Materials and Methods: This research is a cross-sectional study. Authors analyzed 147 urology residents across five urology education centers in Indonesia who fulfilled a self-administered online questionnaire. Participants were asked about their objective and subjective experience regarding urology residency, before and during the COVID-19 pandemic. Results: Change in urology education paradigm in Indonesia during the COVID-19 pandemic is agreed upon by 95.91% participants, 57.82% thinks it brings negative causes negative consequences. Anxiety toward competence level is felt by 70.06% of participants. Reduced opportunities to learn, especially surgical skills may lead to this result. Overall mental health condition of participants does not significantly change. Multiple factors may contribute to this result. Conclusion: As changes and adaptations are inevitable, more attention should be brought to residents' competence level while maintaining COVID-19 prevention protocol. This is the first nationwide survey showing the effects of the COVID-19 pandemic on urology education system in Indonesia. Authors suggest a larg-scale study, with more detailed questionnaire to further elaborate the causes and effects of each variable observed.